Oil Market Developments and Issues. (Policy Papers; Policy Paper, 2005)
The discussion in this paper of the causes and consequences of recent oil price increases, and the appropriate policy response, is framed by the volatility and uncertainty that characterize the oil market. Volatile prices arise from supply and demand that are both highly inelastic in the short run, with the result that even small shocks can have large effects on price. The difficulty of predicting long-run supply and demand creates uncertainty about future prices. Further, even current supply and demand data are lacking, which results in additional uncertainty. These features of uncertainty and volatility of prices make it difficult to reach simple conclusions about how oil producers and consumers should respond to price changes.